2013
DOI: 10.1002/hpm.2183
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare reform in Italy: an analysis of efficiency based on nonparametric methods

Abstract: Over the past twenty years, important changes in the Italian health system have led to different approaches in organizing, delivering and financing health services throughout the regions of the country. This study aims to examine the impact these factors have had on efficiency. The methodology adopted is based on the developments in bootstrapping Data Envelopment Analysis (DEA). In particular, employing a two-stage procedure, we analyzed the impact that political interventions have produced on healthcare effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
0
32
0
1
Order By: Relevance
“…One of these [68] analysed how the different organizational models adopted in Italy’s healthcare services and patient mobility might affect healthcare efficiency at the regional level. The analysis of the regression results indicated that the national reimbursement system produced a significantly negative effect on healthcare efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…One of these [68] analysed how the different organizational models adopted in Italy’s healthcare services and patient mobility might affect healthcare efficiency at the regional level. The analysis of the regression results indicated that the national reimbursement system produced a significantly negative effect on healthcare efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on the Italian healthcare market, which is the specific case study proposed by the authors, we can identify both public and private providers of healthcare services [ 17 20 ]. On the one hand, there are public services currently offered by Local Health Authorities (LHAs) through Family Doctors (FDs), who are responsible for the comprehensive healthcare of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the second stage, we estimated the impact of religious diversity and other explanatory variables on efficiency using truncated regression. As we discuss below, advanced bootstrap techniques were adopted, in line with a growing literature on the determinants of efficiency in the healthcare industry (De Nicola, Gitto and Mancuso, 2012;De Nicola et al, 2014).…”
Section: Methodsmentioning
confidence: 99%